Estudo de extração de C. roseus e produção de nanopartículas para liberação de vimblastina - Falcão, Manuel Alves (2016)
Chemotherapy is highlighted for the treatment of many classes of tumors, especially by new drug delivery nanosystems. The drug delivery nanosystems are focused on greater selectivity for abnormal tissue, decrease adverse effects, dose reduction and decreased frequency applications. Due to the scale of these systems, the EPR effect favors the permeabilization in blood vessels and retention in tumor tissue particles. This thesis performed vinblastine extractions from C. roseus using water and ethanol as co-solvents for CO2 at 300 bar and at different temperatures, those experiments showed the viability of this extraction method, subsequent extractions were optimized using ethanol. The results are compared to traditional extraction methods such as solid-liquid extraction the results found was up to 92.41%. Concluding that vinblastine extraction using carbon dioxide and ethanol mixtures at high pressure is possible. The PLGA nanoparticles containing vinblastine showed again the reproducibility of the nanoemulsion method of ensuring the production of homogeneous nanoparticles with and without drug and cell viability experiments show that the three formulations of PLGA nanoparticles containing vinblastine potentiated drug activity at the lower doses, 1 and 5 μg/mL, compared to free drug. The studies of glycopolymers synthesis presented the novel synthesis of an ATRP initiator based on PLGA without using PEG spacers. This initiator may, in future studies, be used for modifying PLGA. Successive attempts monomer polymerization saccharide via ATRP in water and DMSO leads to the conclusion that this approach is not the most suitable for the syntheses of glycopolymers graft from a PLGA initiator without the use of PEG spacers.